Benchmarking of several material constitutive models for tribology, wear, and other mechanical deformation simulations of Ti6Al4V. (September 2019) - Liu, Cen; Goel, Saurav; Llavori, Iñigo; Stolf, Pietro; Giusca, Claudiu L; Zabala, Alaitz; Kohlscheen, Joern; Paiva, Jose Mario; Endrino, Jose L.; Veldhuis, Stephen C.; Fox Rabinovich, German S.
Abstract: Use of an alpha-beta (multiphase HCP-BCC) titanium alloy, Ti6Al4V, is ubiquitous in a wide range of engineering applications. The previous decade of finite element analysis research on various titanium alloys for numerous biomedical applications especially in the field of orthopedics has led to the development of more than half a dozen material constitutive models, with no comparison available between them. Part of this problem stems from the complexity of developing a vectorised user-defined material subroutine (VUMAT) and the different conditions (strain rate, temperature and composition of material) in which these models are experimentally informed. This paper examines the extant literature to review these models and provides quantitative benchmarking against the tabulated material model and a power law model of Ti6Al4V taking the test case of a uniaxial tensile and cutting simulation.